Support for the Development of Cultural and Art Edutourism in Mentaraman with the POKDARWIS Institution Strengthened by Competencies in Rural Tourism Management - Agung Winarno; Oktavia Sulistiana; Muhammad Nur Singgih; Sopingi Sopingi; Naufal Dzakwana Muhammad; Desti Nur Aini (Journal of Innovation and Community Engagement, 2025)
The arts and culture of each region in Indonesia have unique authenticity, making them difficult to imitate and giving each area its characteristics. This uniqueness can be developed, particularly in tourism. Community participation is crucial in tourism development, making the formation of POKDARWIS essential in areas with tourism potential, such as Mentaraman village. Initial observations show that Mentaraman village has yet to form a POKDARWIS, prompting this study to recommend its establishment. This study outlines the targets and stages needed to form a POKDARWIS, including the preparation, formation, and formalization stages. The planning stage involves mapping the village's potential to identify the need for POKDARWIS. The formation stage begins with information dissemination and agreements among stakeholders. The formalization stage ensures community recognition through relevant agencies. The results demonstrate successful POKDARWIS formation. Positive community responses highlight that the program aligns with their needs, fostering a sense of ownership and enthusiasm for tourism development. This initiative not only meets the community service program output target but also lays the foundation for sustainable tourism practices by integrating local arts and culture into the program's framework.